2020
DOI: 10.1002/ana.25697
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Neuroimaging over 30 Days: Temporal Characteristics of Migraine

Abstract: Objective Although migraine is defined by the headache and headache‐associated symptoms, the true beginning of a migraine attack lies in the premonitory phase. To understand the generation of attacks, one needs to investigate the phase before headache starts. The premonitory phase of migraine is characterized by a well‐described complex of symptoms. Its duration, however, is not clearly defined, and there are no biomarkers to help define when this phase starts. Methods Here, we used functional magnetic resonan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
101
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(112 citation statements)
references
References 29 publications
(84 reference statements)
2
101
0
Order By: Relevance
“…The dynamic alterations of functional connectivity between the hypothalamus and some specific nuclei within the brainstem (e.g. the dorsal pons, and the spinal trigeminal nucleus) have been shown to be responsible for the cyclic nature of migraine attacks (49,50). Also, the hyper-responsiveness to painful trigeminal stimulation in the anterior part of the hypothalamus is involved in migraine chronification (51).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dynamic alterations of functional connectivity between the hypothalamus and some specific nuclei within the brainstem (e.g. the dorsal pons, and the spinal trigeminal nucleus) have been shown to be responsible for the cyclic nature of migraine attacks (49,50). Also, the hyper-responsiveness to painful trigeminal stimulation in the anterior part of the hypothalamus is involved in migraine chronification (51).…”
Section: Discussionmentioning
confidence: 99%
“…Further studies using a longitudinal follow-up design are needed. Finally, given the inherent limitation, SBM is not capable of analyzing subcortical regions (46,47), including the hypothalamus and the brainstem, both of which have been recognized recently to play crucial roles in migraine pathogenesis (48)(49)(50)(51). The dynamic alterations of functional connectivity between the hypothalamus and some specific nuclei within the brainstem (e.g.…”
Section: Limitationsmentioning
confidence: 99%
“…The timeline of the migraine attack documents the sequential development of 4 distinct clinical phases named prodrome, aura, headache, and postdrome. Research in migraine pathophysiology has been focused on the earliest attack’s stage, the premonitory phase, considered “the true beginning of a migraine attack,” as suggested also by recent fMRI evidence of an activation of the anterior‐lateral part of the hypothalamus during the 48 hours preceding pain onset in a longitudinal neuroimaging study with daily sessions over 3 days in 1 migraine patient, an important N = 1 study 22 …”
Section: Clinical Evidencementioning
confidence: 99%
“…Recently, functional neuroimaging studies have suggested that there is early engagement of various brain areas during the premonitory phase; namely the hypothalamus, thalamus, limbic areas, sensory processing cortex and brainstem regions [18][19][20][21][22][23][24]. These areas functionally correlate with commonly reported symptoms during this time, such as thalamus and sensory cortices with photophobia, hypothalamus with homeostatic dysregulation and altered arousal and limbic areas with mood and cognitive change.…”
Section: Introductionmentioning
confidence: 99%